Medullary thyroid carcinoma – Adverse events during systemic treatment: risk-benefit ratio - Maciel,Léa Maria Zanini (2017)
ABSTRACT Medullary thyroid carcinoma (MTC) is a rare neuroendocrine tumor originating from parafollicular C cells of the thyroid and associated with mutations in the proto-oncogene REarranged during Transfection (RET). The prognosis of MTC depends on clinical stage, with a 95.6% 10-year survival rate among patients with localized disease and 40% among patients with advanced disease. Standard chemotherapy and radiotherapy have no significant impact on the overall survival of these patients and two tyrosine kinase receptor inhibitors (TKIs), vandetanib and cabozantinib, have been recently approved for the systemic treatment of locally advanced or metastatic MTC. However, since patients with MTC and residual or recurrent disease may have an indolent course with no need for systemic treatment, and since these drugs are highly toxic, it is extremely important to select the patients who will receive these drugs in a correct manner. It is also essential to carefully monitor patients using TKI regarding possible adverse effects, which should be properly managed when occurring.